Diantimony Complexes [CpR2Mo2(CO)4(μ, η2‐Sb2)] (CpR=C5H5, C5H4tBu) as Unexpected Ligands Stabilizing Silver(I)n (n=1–4) Monomers, Dimers and Chains. Issue 7 (11th January 2023) - Shelyganov, Pavel A.; Elsayed Moussa, Mehdi; Seidl, Michael; Scheer, Manfred
Abstract: Synthesis and reactivity of transition metal compounds bearing "naked" pnictogen atoms is an active research area with remarkable bonding patterns observed in the formed compounds. Within this field, intense investigations on the coordination behavior of complexes possessing P n and As n (2≤ n ≤5) moieties have been conducted. However, studies on heavier analogues have been ignored so far due to arduous challenges related to low yields and moderate air stability. Herein, we present the first in‐depth study addressing the reactivity of organometallic complexes containing Sb‐donor atoms with several Ag I salts. These reactions afforded twelve unprecedented aggregates as monomers, dimers as well as three‐ and four‐membered chains of Ag I ions claimed in the literature to be inaccessible. Interatomic distances as well as computational evidence obtained with help of several different methods suggest the presence of Ag⋅⋅⋅Ag interactions in all complexes containing more than one Ag I ion. Abstract : The first study of the coordination behavior of tetrahedrane Sb‐donor complexes towards Ag I salts afforded twelve unprecedented supramolecular aggregates as monomers, dimers as well as three‐ and four‐membered chains of Ag I . Pathways for the assembling processes were suggested based on manifold solution studies and the presence of argentophilic interactions in compounds containing two or more Ag I ions was confirmed by DFT calculations.